The personal jurisdiction of the Arab court for human rights compared to the European court of human rights - Al-Dabbas, Ali Muhammad; Al-Momani, Sayel Mufleh; Helo, Shady Helo Abu; Qaisi, Abeer Al; Abuelzeet, Rehan; Al-Andali, Mohammad Moqbel (Edelweiss Applied Science and Technology, 2024)
The research dealt with the personal jurisdiction of the Arab Court for Human Rights compared to the European Court of Human Rights, by indicating who are the natural persons and legal persons who are entitled to file claims and the conditions for their acceptance with the two courts, adopting the analytical approach and the comparative approach to find out the deficiencies in the statute of the Arab Court for Human Rights and address them. Several results and proposals were reached. As for the most important results, they are represented by the narrowing of the scope of personal jurisdiction in the statute of the Arab Court for Human Rights and confining it mainly to the states parties to the Arab Charter for Human Rights, and on the condition that there is a personal interest for the state in the case, while the scope of personal jurisdiction in the European Court of Human Rights has expanded to include the states parties to The European Convention on Human Rights without the existence of a personal interest and any individual, non-governmental organization or group of persons, and that the jurisdiction of the Arab Court of Human Rights is optional, while we find it compulsory at the European Court of Human Rights. As for the most important proposals, it is represented by amending the text of Article (19) of the statute of the Arab Court for Human Rights, to expand the scope of personal jurisdiction, by defining the right of individuals, non-governmental organizations, and a group of persons to file lawsuits in response to the development of the individual’s status in international law. Also, amending the statute of the Arab Court for Human Rights, by adding a provision that makes the court’s jurisdiction compulsory in all cases.